2014
DOI: 10.3109/15368378.2013.869755
|View full text |Cite
|
Sign up to set email alerts
|

Epinephrine, DNA integrity and oxidative stress in workers exposed to extremely low-frequency electromagnetic fields (ELF-EMFs) at 132 kV substations

Abstract: There is apprehension about widespread use of electrical and electromagnetic gadgets which are supposed to emit electromagnetic radiations. Reports are controversy. These electromagnetic fields (EMFs) have considerable effect on endocrine system of exposed subjects. This study was focused to assess the possible bioeffects of extremely low-frequency (ELF)-EMFs on epinephrine level, DNA damage and oxidative stress in subjects occupationally exposed to 132 kV high-voltage substations. The blood sample of 142 expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 31 publications
2
18
0
Order By: Relevance
“…For example, Frahm et al reported that 24 h of exposure to 50-Hz ELF-MF at 1 mT elevated phagocytic activity and the intracellular ROS level in the absence of any genotoxic effects (Frahm et al, 2010). In addition, 50-Hz ELF-EMF is able to potentiate the cellular damage induced by oxidative stress in humans (Tiwari et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…For example, Frahm et al reported that 24 h of exposure to 50-Hz ELF-MF at 1 mT elevated phagocytic activity and the intracellular ROS level in the absence of any genotoxic effects (Frahm et al, 2010). In addition, 50-Hz ELF-EMF is able to potentiate the cellular damage induced by oxidative stress in humans (Tiwari et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…The widespread use of electricity in domestic and industrial settings highlights the importance of investigating the biological effects of ELF electric fields (EFs), particularly at the 50-and 60-Hz power-line frequencies [Hjeresen et al, 1980;Jaffe et al, 1980;Marino et al, 1980;WHO, 2008;Akpinar et al, 2012;Gok et al, 2014Gok et al, , 2016Tiwari et al, 2015;Zhang et al, 2016]. The widespread use of electricity in domestic and industrial settings highlights the importance of investigating the biological effects of ELF electric fields (EFs), particularly at the 50-and 60-Hz power-line frequencies [Hjeresen et al, 1980;Jaffe et al, 1980;Marino et al, 1980;WHO, 2008;Akpinar et al, 2012;Gok et al, 2014Gok et al, , 2016Tiwari et al, 2015;Zhang et al, 2016].…”
Section: Introductionmentioning
confidence: 99%
“…Biological studies on extremely-low-frequency (ELF) electromagnetic fields generally have two perspectives: health risk and clinical application. The widespread use of electricity in domestic and industrial settings highlights the importance of investigating the biological effects of ELF electric fields (EFs), particularly at the 50-and 60-Hz power-line frequencies [Hjeresen et al, 1980;Jaffe et al, 1980;Marino et al, 1980;WHO, 2008;Akpinar et al, 2012;Gok et al, 2014Gok et al, , 2016Tiwari et al, 2015;Zhang et al, 2016]. However, ELF EFs have been applied in clinical treatment and health maintenance, including in medical facilities and homes, for at least half a century in Japan [Hara, 1961;Ito, 2000;Shinba et al, 2012;Harakawa et al, 2014;Mitani et al, 2015].…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous other examples in the scientific literature. • The study of Tiwari et al (2015) only reported a tendency to higher DNA damage levels in substation workers reflecting over interpretation of the data rather than a real effect. • The value of cytogenetic biomonitoring studies is, amongst others, largely dependent on two important parameters, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…According to the authors, chronic occupational exposure to EMFs may lead to an increased risk of genetic damage among the electrical workers. Tiwari et al (2015) used the alkaline comet assay to investigate DNA damage in cells from workers at 132 kV substations who were exposed to ELF-EMFs for more than 2 years. Blood sample of 142 exposed subjects and 151 non-exposed individuals was analysed.…”
Section: Cytogenetic Investigations Of Human Subjects Occupationally mentioning
confidence: 99%